2006
DOI: 10.1038/sj.mp.4001793
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-resistant bipolar disorder

Abstract: Despite the remarkable increase in medications validated as effective in bipolar disorder, treatment is still plagued by inadequate response in acute manic or depressive episodes or in long-term preventive maintenance treatment. Established first-line treatments include lithium, valproate and second-generation antipsychotics (SGAs) in acute mania, and lithium and valproate as maintenance treatments. Recently validated treatments include extended release carbamazapine for acute mania and lamotrigine, olanzapine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 114 publications
0
105
0
5
Order By: Relevance
“…Lithium salts exert two therapeutic effects: an acute antimanic action and a delayed mood-stabilizing and phase prophylactic action, which requires chronic treatment of up to several months (Gitlin, 2006). The latter one is assumed Figure 4 Effect of lithium on CREB Ser 133 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium salts exert two therapeutic effects: an acute antimanic action and a delayed mood-stabilizing and phase prophylactic action, which requires chronic treatment of up to several months (Gitlin, 2006). The latter one is assumed Figure 4 Effect of lithium on CREB Ser 133 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition, particularly environmental influences such as chronic stress are assumed to precipitate the disease (Johnson, 2005). Among the drugs recommended for the treatment of bipolar disorder, lithium salts are of prime importance (Gitlin, 2006). Lithium has been discovered more than 50 years ago as a drug with an acute antimanic action (Cade, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although mood stabilizers such as lithium (Li), valproate (VPA), carbamazepine (CBZ), and lamotrigine (LTG) are commonly used for treatment of BD patients (Goodwin, 2003), their effects are often inadequate. Moreover, many BD patients have suffered from pervasive and chronic symptoms, multiple episode recurrences and marked functional disability (Giltin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review that included 15 clinical trials showed that clozapine was associated with improvement in social functioning [23]. It is worth mentioning that clozapine may be also effective for treatment-resistant patients with bipolar disorder [23][24][25]. Despite proven effectiveness in bipolar disorder, there are concerns regarding some significant side effects, including agranulocytosis, myocarditis, cognitive disturbances, and weight gain.…”
Section: Functioning and Neurocognitive Impairmentmentioning
confidence: 99%